2011
DOI: 10.1002/ar.21527
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Topographical Anatomy of the Upper Abdominal Lymphatics: Its Specific Features in Comparison With Other Abdominopelvic Regions

Abstract: Using semiserial sections from 19 human fetuses of 8-30 weeks gestation, we examined the topohistology of the upper abdominal lymphatics and compared it with that of the lower abdominal and pelvic lymphatics. The upper abdominal lymphatics were characterized by an intimate relationship with the peritoneal lining, a common mesentery for the celiac trunk and superior mesenteric artery (SMA). Lymphatic connections from the upper abdominal viscera to the paraaortic and paracaval areas followed two routes: (1) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…Rather, immature lymphocytes likely proliferate in mesenteric lymph nodes. In contrast to cervical, mediastinal and pelvic nodes, the masses of mesenteric nodes increase markedly in late stage human fetuses in and along the peritoneal fusion at territories of the celiac and superior mesenteric arteries (Kim et al, ). We hypothesized that, at least in humans, primitive lymphocytes originating from around the yolk sac blood island first move to the mesenteric nodes, not to the liver, spleen and/or intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, immature lymphocytes likely proliferate in mesenteric lymph nodes. In contrast to cervical, mediastinal and pelvic nodes, the masses of mesenteric nodes increase markedly in late stage human fetuses in and along the peritoneal fusion at territories of the celiac and superior mesenteric arteries (Kim et al, ). We hypothesized that, at least in humans, primitive lymphocytes originating from around the yolk sac blood island first move to the mesenteric nodes, not to the liver, spleen and/or intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the abdominal alimentary canal wall was rich in LVs, whereas the esophagus was not. These findings indicated that fetal LVs are not a miniature version of adult LVs, findings supported by later detailed examination conducted along and around the fetal lesser sac (Kim et al. in press).…”
Section: Introductionmentioning
confidence: 55%
“…Submesothelial fibrous components were fewer in and along the liver and abdominal gastrointestinal tract than the lung in a same section. The thin submesothelial tissue in the abdomen might be a result of no or few veins and lymphatics contained [1819]. The subpleural fibers might conduct mechanical stress from the thoracic wall to the lung ECM with or without modification.…”
Section: Discussionmentioning
confidence: 99%